Physical development of children at Gorzów Wlkp. - Zwoliński, Lucjan (Anthropological Review, 1974)
The results of research concerning the physical development of children at Gorzów Wlkp. have been presented. The children were examined twice, for the first time in 1947 and 20 years later in 1967. In both series the age of the examined subjects was from 8 - 15. A comparative analysis of changes in the studied characteristics over these 20 years (1947 - 1967) has been carried out. The found differences had more distinctly manifested themselves in the group of boys. They were in stature 11.16 cm and in weight 7.18 kg. In the group of girls these values are somewhat smaller and amount for stature to 10.06 cm and for weight to 5.64 kg.